PARTISIPASI POLITIK MASYARAKAT DALAM PENGAMBILAN KEPUTUSAN PENGGUNAAN DANA DESA DI DESA BANDAR KLIPPA - Sri Rejeky Sitohang; Adinda Putri Br Sitepu; Julia Ivanna (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study examines community political participation in decision-making regarding the use of Village Funds in Bandar Klippa Village, Percut Sei Tuan District, Deli Serdang Regency. The problem in this study is the persistent variation in the level of community participation in village deliberations and decision-making regarding the use of Village Funds. The purpose of this study is to determine the forms of community participation and the factors influencing this participation. This study used a descriptive method with a qualitative approach. Data were obtained through interviews with five informants, observation, and documentation. Data analysis was carried out through data reduction, data presentation, and conclusion drawing. The results show that community participation is evident through attendance at village deliberations, submission of proposals, suggestions, and opinions regarding village development programs. Community participation is considered quite good, but is influenced by factors such as awareness, education, information from the village government, trust in the village government, and community busyness.